Assessment of the Efficacy of Photobiomodulation (PBM) Therapy in Periodontal Treatment: A Longitudinal Study - Niladri Maiti; Stefano Benedicenti; Sumalatha Appam; Irfa Junaid; Divyatammana; Pooja Kadam; Tohid Ali (Wolters Kluwer Medknow Publications, 2024)
Objective: The intention of this longstanding study was to assess the effectiveness of photobiomodulation (PBM) therapy as a complementary periodontal therapy method. Methods: Fifty patients with periodontal disease were recruited and randomly randomized to receive either PBM therapy (n = 50) or traditional periodontal management (n = 50) as the control group. Periodontal parameters were measured at baseline and 3 and 6 months after management, including gingival index, probing depth, and clinical attachment level. Statistical analysis was applied. Results: At follow-up intervals, both the PBM management group and the control group showed significant improvements in periodontal markers. The PBM therapy group confirmed a higher degree of improvement than the control group, with statistically significant variations between the groups at 3 and 6 months post management (P < 0.05). Conclusion: In summary, PBM therapy outperforms traditional management techniques in terms of improving periodontal metrics. The incorporation of PBM therapy as an additional therapeutic method for the management of periodontal disease into clinical practice is supported by these findings. To improve management procedures and clarify the longstanding impacts of PBM therapy on periodontal tissue regeneration and clinical results, more investigation is necessary.